Conceiving the (everyday) landscape of energy as a transcalar infrastructural device - Daniela Perrotti (Projets de Paysage)
This paper’s goals are twofold. It introduces and explores, through a step-by-step demonstration process, a fundamental hypothesis, concerning the possibility of reading the everyday landscape of energy as an infrastructural device, able to support different ways, for social actors, researchers and professionals, of experimenting with new forms of interaction between geographic and socio-political scales. Complementarily, the article proposes the contextualization of this hypothesis within the debate which originated after the publication in February 2010 of the second issue “Landscapes of Energy” of the Harvard GSD journal New Geographies (editor-in-chief: arch. Rania Ghosn). Introducing the scientific hypothesis of “thinking energy spatially”, and discussing the provocative statement “energy is a spatial product”, the various articles collected in this journal propose different approaches to the historicization of “the dialectical relation between energy and society.”